Clinical impact of the prognostic nutritional index and skeletal muscle index for the incompletion of adjuvant chemotherapy for pancreatic cancer - Hiromitsu Maehira; Haruki Mori; Nobuhito Nitta; Takeru Maekawa; Yusuke Nishina; Hajime Ishikawa; Katsushi Takebayashi; Sachiko Kaida; Toru Miyake; Masaji Tani (Asian Journal of Surgery)
Background: Adjuvant chemotherapy is a standard therapeutic option for resected pancreatic cancer. However, the risk factors for incompletion of adjuvant chemotherapy remain unclear. Methods: We retrospectively reviewed the medical records of 72 patients who underwent radical pancreatectomy and received S-1 adjuvant chemotherapy for pancreatic cancer. The patients were assigned to two groups according to their completion or incompletion of adjuvant chemotherapy. We compared the perioperative skeletal muscle mass index (SMI) and nutritional status using prognostic nutritional index (PNI) between the two groups. Results: The completion and incompletion groups included 46 (64 %) and 26 (36 %) patients, respectively. Overall survival was shorter in the incompletion group than in the completion group (median survival time, 20.2 months vs. 42.0 months; log-rank, p = 0.018). Decreasing rate of PNI (12.7 % vs. 0.2 %, p = 0.010) and decreasing rate of SMI (26.9 % vs. 12.5 %, p = 0.001) were significantly larger in the incompletion group than in the completion group. Multivariate analysis showed that decreasing rate of PNI (p = 0.016), decreasing rate of SMI (p = 0.013), and old age (p = 0.049) were independent risk factors for incompletion of S-1 adjuvant chemotherapy. Regarding the time-series variations, PNI improved from 1 to 3 months after pancreatectomy in the completion group (p = 0.006). Furthermore, the decreasing slope of SMI was stronger in the incompletion group. Conclusion: Postoperative decrease of PNI and SMI is associated with the incompletion of S-1 adjuvant chemotherapy.